Adding and Subtracting Polynomials

5m + 12n^2 + 6n - 8m

-6x^3 + 5x + 2x^3 + 4x^3

3b^3 - 2b - 1 - b^3 - b

(-7x^2 - 2x +3) + (4x^2 - 9x)

(3x^2 - x) - (x^2 + 3x - x)

(3s^2 + 4s) - (-10s^2 + 6s)

5 answers

1. -3m + 12n^2 + 6n
2. 3x + 3x^3
3. 2b^3 - 3b - 1
4. -3x^2 - 11x + 3
5. 2x^2 - 4x
wrong yet again!
#2. -6x^3 + 5x + 2x^3 + 4x^3 = 3x^3 + 5x
#6. (3s^2 + 4s) - (-10s^2 + 6s) = 13s^2 - 2s
Apologies for the mistakes in my previous responses. Thank you for the corrections. Here are the correct results:

2. -6x^3 + 5x + 2x^3 + 4x^3 = 3x^3 + 5x
6. (3s^2 + 4s) - (-10s^2 + 6s) = 13s^2 - 2s
Adding and Subtracting Polynomials
17. 5m + 12n^2 + 6n - 8m

21. -6x^3 + 5x + 2x^3 + 4x^3

24. 3b^3 - 2b - 1 - b^3 - b

26. (-7x^2 - 2x +3) + (4x^2 - 9x)

28. (-2z^3 + z + 2z^3 + z) + (3z^3 - 5z^2)

30. (3x^2 - x) - (x^2 + 3x - x)

32. (3s^2 + 4s) - (-10s^2 + 6s)
17. 5m + 12n^2 + 6n - 8m = -3m + 12n^2 + 6n
21. -6x^3 + 5x + 2x^3 + 4x^3 = 5x - x^3
24. 3b^3 - 2b - 1 - b^3 - b = 2b^3 - 3b - 1
26. (-7x^2 - 2x +3) + (4x^2 - 9x) = -3x^2 - 11x + 3
28. (-2z^3 + z + 2z^3 + z) + (3z^3 - 5z^2) = z^3 - 5z^2 + 2z
30. (3x^2 - x) - (x^2 + 3x - x) = 2x^2
32. (3s^2 + 4s) - (-10s^2 + 6s) = 13s^2 - 2s